Sustainability Business Model: A Case Study of The Evolution of Activity System by Eco-Design and Eco-Innovation Practices to Value Wine Production - Hiam Serhan; Gwenola Yannou-Le Bris (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
This paper represents a case study research that considers business model from a practice and dynamic perspective. It studies the transformation of the business model of a French Château that produces and values wine through a green strategy. It shows how the implementation of eco-conception and eco-innovation practices has provided it a differentiating sustainable value added and reinforced its strategic position. Arguments are exposed in three sections. The first discusses business model sustainability according to the normative approach and the partnership theory. By these complementary concepts we show how imperatives of ecological sustainability and business activities are worked out on the business model level. This perspective reveals not only the value proposition to customers, but also the value-creating constellation in which a firm connects to different partnerships and acquires tangible and intangible resources in a profitable manner. These approaches to sustainability are considered as essential drivers of eco-innovations. The second section illustrates the case study. Data is obtained from secondary sources and semi-directive interviews. It is analysed and interpreted with the theoretical model of the activity system and expansive learning of Engeström (2001, 2015). This model illustrates how an activity system moves from an initial business model to a more sustainable state by the mediation of artefacts (standards, formal and informal rules) and partnerships (community) to collectivelyconstruct and propose a meaningful object (sustainable wine). In the third and last section, we discuss the obtained results. We show how standards requirements and partnerships involved in the sustainable business model allowed the creation of a distinctive value to the product in the market.
Keywords: 650; Business model; Sustainability; Eco-conception; Eco-innovation; Value creation